2015
DOI: 10.3109/10253890.2015.1058356
|View full text |Cite
|
Sign up to set email alerts
|

High cortisol awakening response is associated with impaired error monitoring and decreased post-error adjustment

Abstract: The cortisol awakening response (CAR), a rapid increase in cortisol levels following morning awakening, is an important aspect of hypothalamic-pituitary-adrenocortical axis activity. Alterations in the CAR have been linked to a variety of mental disorders and cognitive function. However, little is known regarding the relationship between the CAR and error processing, a phenomenon that is vital for cognitive control and behavioral adaptation. Using high-temporal resolution measures of event-related potentials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…One of the most common measures to investigate response inhibition is the classical Go/NoGo task. The procedures followed the protocol of previous studies performed in our laboratory (Ma et al, 2015;Wu et al, 2017;Zhang et al, 2015). The only difference in the current study is that we did not use O/X but the digit 1/9 as the stimulus.…”
Section: Go/nogo Taskmentioning
confidence: 99%
“…One of the most common measures to investigate response inhibition is the classical Go/NoGo task. The procedures followed the protocol of previous studies performed in our laboratory (Ma et al, 2015;Wu et al, 2017;Zhang et al, 2015). The only difference in the current study is that we did not use O/X but the digit 1/9 as the stimulus.…”
Section: Go/nogo Taskmentioning
confidence: 99%
“…Previous research suggests that witnessing or being a victim of violence during adolescence may be linked to poor development of future orientation (Monahan et al, 2015) and this research is particularly relevant in light of the physical abuse/violence and CAR association finding in the current study. Previous research has also found a similar negative association between CAR and error monitoring (Zhang et al, 2015). Error monitoring, an important aspect of adaptive cognition, allows for behavioural adjustments that prevent future mistakes in goal-directed action via the implementation of cognitive control (Alexander and Brown, 2010).…”
Section: Discussionmentioning
confidence: 65%
“…Arnsten, 2009;Brown et al, 2005;Izquierdo et al, 2006). However, findings from studies examining the relationship between the CAR and EF have been inconsistent with some studies showing positive associations (working memory: Almela et al, 2012;attention switching: Evans et al, 2012;Law et al, 2015), some showing negative associations (error monitoring: Zhang et al, 2015), some showing no association (working memory, attention switching and cognitive inhibition: Franz et al, 2011;working memory: Ennis et al, 2016;Hidalgo et al, 2016) or a more complex U-shaped relationship (working memory: Moriarty et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, previous studies found that task parameters, such as the response-stimulus interval [ 35 ] and task instructions [ 36 ], affect the presence and magnitude of PES. For example, PES is reduced when task instructions emphasize response speed [ 36 , 37 , 38 , 39 ]. In the present study, the instructions for the Go/No-go task also emphasized speed, which may have led to the diminished PES effect at the group level.…”
Section: Discussionmentioning
confidence: 99%